A Novel Method to Improve Perfusion of Ex Vivo Pumped Human Kidneys. Issue 6 (December 2021) - Zhu, Lin; Qureshi, Arshna; Awad, Mohamed; Hausladen, Alfred; Perez-Protto, Silvia; Latifi, Samir Q.; Lebovitz, Daniel J.; Chavin, Kenneth; Stamler, Jonathan S.; Reynolds, James D.
Abstract : Objective: To determine if addition of the S-nitrosylating agent ethyl nitrite (ENO) to the preservation solution can improve perfusion parameters in pumped human kidneys. Background: A significant percentage of actively stored kidneys experience elevations in resistance and decreases in flow rate during the ex vivo storage period. Preclinical work indicates that renal status after brain death is negatively impacted by inflammation and reduced perfusion—processes regulated by protein S-nitrosylation. To translate these findings, we added ENO to the preservation solution in an attempt to reverse the perfusion deficits observed in nontransplanted pumped human kidneys. Methods: After obtaining positive proof-of-concept results with swine kidneys, we studied donated human kidneys undergoing hypothermic pulsatile perfusion deemed unsuitable for transplantation. Control kidneys continued to be pumped a 4°C (ie, standard of care). In the experimental group, the preservation solution was aerated with 50 ppm ENO in nitrogen. Flow rate and perfusion were recorded for 10 hours followed by biochemical analysis of the kidney tissue. Results: In controls, perfusion was constant during the monitoring period (ie, flow rate remained low and resistance stayed high). In contrast, the addition of ENO produced significant and sustained reductions in resistance and increases in flow rate. ENO-treated kidneys had higher levels of cyclic guanosine monophosphate, potentially explaining the perfusion benefits, and increased levels of interleukin-10, suggestive of an anti-inflammatory effect. Conclusions: S-Nitrosylation therapy restored the microcirculation and thus improved overall organ perfusion. Inclusion of ENO in the renal preservation solution holds promise to increase the number and quality of kidneys available for transplant. Abstract : Supplemental Digital Content is available in the text